How employees can break out of their learning comfort zone in green innovation scenarios: a nudging experiment based on the pressures of sustainable development in China - Shuming Li; Chuanxi Yang; Guangyu Zhai (Frontiers in Psychology)
The use of nudging tools to motivate employees to actively participate in corporate green innovation has not yet received sufficient attention. Designing and implementing effective nudging strategies to push employees out of their comfort zones and actively learning green knowledge can bridge the research gap based on the expectancy theory. In this study, 2,253 participants from Chinese manufacturing firms were divided into five groups to investigate the effect of different nudges on green knowledge acquisition. The findings indicate that the combined nudges of social norm and social status have a greater impact than their individual counterparts, and there is no evidence of a crowding out effect. It is more meaningful for employee learning and corporate green development that the efficacy of praising before pressuring is greater in the two combined interventions. Furthermore, we revalidated the efficacy of nudging tactics by carrying out robustness tests and heterogeneity verification for subdivided samples of enterprise ownership and employee position. This study offers a viable operational pathway for theoretical research and business practice on green innovation. We are willing to suggest that stakeholders devote more effort to studying various types of innovation nudging methods.